Role of functional relations in the identification of regions (Journal of Planner and Development, 2007)
The region is defined by the spatial dimension, which consists of a set of stabilizers (towns and villages). The concept of the territory requires conditions on the nature of functional relations and the mutual influence of the regions within the region. Any territory must be based on the interdependence and interaction between the mother city and its surrounding countryside and cities, and when the interdependence is strong and the interaction is clear, it helps to define the territory. The regions are divided on different bases. There are geographically or national homogeneous regions, and there are cultural regions that want to preserve their culture in terms of language or religion. There are administrative regions to manage the place, economic regions dependent on natural resources, and there are regions centered around major cities Or metropolitan cities. Article 115 of the Constitution stipulates the following: Each governorate or more shall have the right to form a territory upon request in the referendum. The question at this stage: What is the extension that defines the borders of the region? Can the administrative boundaries of the provinces determine the territory? How can a solution be achieved if a particular governorate, city or sub-region wants to join this or that territory? For the purposes of this research, the city of Mahmudiyah was selected as a model to identify the subject of the borders of the region, especially since it passed through the previous period to more than a process of administrative change, it is sometimes within the administrative boundaries of the province of Baghdad and other times within the administrative boundaries of the province of Babylon, as happened in 1987, To the province of Baghdad in the early nineties. Some statistical and mathematical methods were used for the purpose of measuring the city’s territory and the areas of influence of major cities, in the hope of future adoption in the identification of regions.